Visita escolar: um recurso do psicodiagnóstico interventivo na abordagem fenomenológico-existencial - Maichin, Vanessa (2006)
The goal of this dissertation is to reflect about the school visit, a procedure that is part of the interventional psychodiagnosis of children within the existential phenomenological approach. The challenge of this work is to start with a familiar phenomenon, already known by the author, the school visit, and then, return to it, but now by analyzing the details of this resource that make possible a wider comprehension of the child and of the parents in the psychodiagnosis process. Theoretical bases about the school universe intercalated with some short cases attended by the author, as well as a clinical case, make it possible to emphasize the importance of the school visit in the psychodiagnosis process. School has a meaningful value in the child s life, because it is within this new social group, composed of different human relationships, that the child composes a new meaningful network. An understanding of the child s relationships with the teacher, classmates and other school professionals enlarges the psychological understanding of the child. The relationship between the parents and the school, and the expectations that they reveal about the institution, expands the psychologist s understanding of the family dynamic. The learning approaches, the physical areas and interlocution spaces are also considered in this work, because they reveal important aspects of the child and the parents